Haploinsufficiency of MYBPC3 exacerbates the development of hypertrophic cardiomyopathy in heterozygous mice. (February 2015) - Barefield, David; Kumar, Mohit; Gorham, Joshua; Seidman, Jonathan G.; Seidman, Christine E.; de Tombe, Pieter P.; Sadayappan, Sakthivel
Abstract: Mutations in MYBPC3, the gene encoding cardiac myosin binding protein-C (cMyBP-C), account for 40% of hypertrophic cardiomyopathy (HCM) cases. Most pathological MYBPC3 mutations encode truncated protein products not found in tissue. Reduced protein levels occur in symptomatic heterozygous human HCM carriers, suggesting haploinsufficiency as an underlying mechanism of disease. However, we do not know if reduced cMyBP-C content results from, or initiates the development of HCM. In previous studies, heterozygous (HET) mice with a MYBPC3 C′-terminal truncation mutation and normal cMyBP-C levels show altered contractile function prior to any overt hypertrophy. Therefore, this study aimed to test whether haploinsufficiency occurs, with decreased cMyBP-C content, following cardiac stress and whether the functional impairment in HET MYBPC3 hearts leads to worsened disease progression. To address these questions, transverse aortic constriction (TAC) was performed on three-month-old wild-type (WT) and HET MYBPC3 -truncation mutant mice and then characterized at 4 and 12 weeks post-surgery. HET-TAC mice showed increased hypertrophy and reduced ejection fraction compared to WT-TAC mice. At 4 weeks post-surgery, HET myofilaments showed significantly reduced cMyBP-C content. Functionally, HET-TAC cardiomyocytes showed impaired force generation, higher Ca 2 + sensitivity, and blunted length-dependent increase in force generation. RNA sequencing revealed several differentially regulated genes between HET and WT groups, including regulators of remodeling and hypertrophic response. Collectively, these results demonstrate that haploinsufficiency occurs in HET MYBPC3 mutant carriers following stress, causing, in turn, reduced cMyBP-C content and exacerbating the development of dysfunction at myofilament and whole-heart levels. Highlights: Surgical stress in Het MYBPC3 mice causes reduced cMyBP-C levels. Decreased cMyBP-C is associated with decreased contractility following TAC. Haploinsufficiency of cMyBP-C with cardiac stress aggravates HCM.